ANALISIS KESALAHAN SISWA SMK DALAM MENYELESAIKAN SOAL MATEMATIKA BERDASARKAN ANALISIS KESALAHAN NEWMAN - Siti Imamatur Rohmah; Soffil Widadah; Eka Nurmala Sari Agustina (Program Studi Pendidikan Matematika STKIP PGRI Sidoarjo, 2021)
This qualitative descriptive study aims to describe the results of the analysis of the errors of vocational students in solving mathematical problems of the three-variable linear equation system. This research was conducted in SMK Persatuan 1 in Tulangan in the year of 2019/2020 in X grade of clothing class. Subjects were chosen based on the number of mistakes made in solving the problems. As for the technique of collecting data in this research were used test and interview method. The test was done to all of the students of the X grade of clothing class. From the outcome of the test was taken 3 subjects who has the most mistaken. Furthermore the chosen subject to be interviewed. The results of the test and interview were analyzed by using Newman error analysis that is reading error, understanding error, transform error, process skill error and final answer error. Based on the research by using Newman error analysis can be concluded that student did the reading error with the error form of unable to read the important words found in the question, students did the understanding error with the error form of unable to write what is known and what is asked and write it but wrong, student did the transform error with the error form of unable to make the mathematical model, students did the process skill with the error form of unable to to solve the problem and incompatible procedure, and student did the final answer error with error form of written error answer and did not write the answer.